Actividad física, indicadores antropométricos y riesgo cardiometabólico de adultos atendidos en la IPRESS-I-4 San Juan de Miraflores, 2023 - Medina Sandoval, Kiara Almendra (2024)
The aim of the study was to determine the relationship between anthropometric indicators, physical activity and cardiometabolic risk in patients treated at the IPRESS I-4 "San Juan de Miraflores". The study was a non experimental, descriptive, cross-sectional correlational study. The sample consisted of 362 patients seen at the general medicine outpatient clinic. An anthropometric indicators sheet, the international physical activity questionnaire and a cardiometabolic risk questionnaire were used as data collection instruments. The results show that for the anthropometric indicator BMI, 33.9% of women and 12.0% of men are in the overweight category. For cardiovascular disease risk according to abdominal circumference, 27.3% of women and 18.2% of men are in the low risk category; 28.2% of women and 3.9% of men are at very high risk. Of the waist-to-hip ratio, 8.3% are in the very low risk category. According to the percentage of fat, in the low category only women have a percentage of 4.1%. In the normal category, women have a significantly high percentage of 28.5%, while men have 6.4%. Of the physical activity the highest percentage has low activity with 29.8% females and 8.6% males. In the very high physical activity category, 20.7% of women and 9.4% of men. Of the cardiometabolic risk, 71.5% of women and 24.0% of men had a high risk, 3.3% of women and 1.1% of men had a moderate risk. None of those evaluated had a low risk. The study concludes that there is a statistical relationship between the anthropometric indicators of BMI, abdominal circumference, waist-hip ratio and cardiometabolic risk.